2019
DOI: 10.1093/imrn/rnz233
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Strong Approximation on the Sphere

Abstract: By assuming some widely believed arithmetic conjectures, we show that the task of accepting a number that is representable as a sum of $d\geq 2$ squares subjected to given congruence conditions is NP-complete. On the other hand, we develop and implement a deterministic polynomial-time algorithm that represents a number as a sum of four squares with some restricted congruence conditions, by assuming a polynomial-time algorithm for factoring integers and Conjecture 1.1. As an application, we develop and implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The second named author formulated a conjecture on the optimal exponent for strong approximation for quadratic forms in 4 variables [Tal15b, Conjecture 1.9] that implies the diameter of LPS Ramanujan graphs is asymptotic to 4/3 log d−1 (n). More recently, he developed and implemented a polynomial time algorithm for navigating LPS Ramanujan graphs under a polynomial time algorithm for factoring integers and an arithmetic conjecture on the distribution of numbers representable as a sum of two squares [Sar17]. The numerical results from that algorithm strongly support that the diameter of LPS Ramanujan graphs is asymptotic to 4/3 log d−1 (n); see [Sar17].…”
mentioning
confidence: 98%
“…The second named author formulated a conjecture on the optimal exponent for strong approximation for quadratic forms in 4 variables [Tal15b, Conjecture 1.9] that implies the diameter of LPS Ramanujan graphs is asymptotic to 4/3 log d−1 (n). More recently, he developed and implemented a polynomial time algorithm for navigating LPS Ramanujan graphs under a polynomial time algorithm for factoring integers and an arithmetic conjecture on the distribution of numbers representable as a sum of two squares [Sar17]. The numerical results from that algorithm strongly support that the diameter of LPS Ramanujan graphs is asymptotic to 4/3 log d−1 (n); see [Sar17].…”
mentioning
confidence: 98%
“…The main motivation for studying w p (a) for a ∈ S d−2 (Z/qZ) ⊂ S d (Z/qZ) comes from the navigation algorithms for the LPS Ramanujan graphs X p,q , and its archimedean analogue which is the Ross and Selinger algorithm for navigating P SU (2) with the golden quantum gates; see [LPS88], [Mar88], [PLQ08], [Sar17a], and also [RS16] and [PS18].…”
mentioning
confidence: 99%
“…The numerical results of Ross and Selinger [RS16] and the third author [Sar17a,Sar18] suggests that for all but tiny fractions of a ∈ S 1 (Z/qZ) ⊂ S 3 (Z/qZ), we have w p (a) = 1 + o q (1). It is also observed that max a (w p (a)) = 4/3 + o q (1).…”
mentioning
confidence: 99%
“…Giving sharp upper bound of this form on the least prime or the least integer representable by a sum of two squares is crucial in the analysis of the complexity of some algorithms in quantum compiling. In particular, Ross and Selinger's algorithm for the optimal navigation of z-axis rotations in SU (2) by quantum gates [RS14] and its p-adic analogue for finding the shortest path between two diagonal vertices of LPS Ramanujan graphs [Sar17]. In [Sar17], we proved that these heuristic algorithms run in polynomial time under a Cramér type conjecture on the distribution of the inverse image of the integers representable as a sum of two squares by a binary quadratic from; see [Sar17, Conjecture 1.4.].…”
mentioning
confidence: 99%
“…In particular, Ross and Selinger's algorithm for the optimal navigation of z-axis rotations in SU (2) by quantum gates [RS14] and its p-adic analogue for finding the shortest path between two diagonal vertices of LPS Ramanujan graphs [Sar17]. In [Sar17], we proved that these heuristic algorithms run in polynomial time under a Cramér type conjecture on the distribution of the inverse image of the integers representable as a sum of two squares by a binary quadratic from; see [Sar17, Conjecture 1.4.]. In this paper, we fix the fundamental discriminant D < 0, and prove that by assuming the generalized Riemann hypothesis a form of this Cramér type Date: May 7, 2018.…”
mentioning
confidence: 99%